Insight into the crystal structure and photoluminescence properties of an extremely broadband yellow-emitting phosphor Sr8MgCe(PO4)7:Eu2+. Issue 3 (23rd December 2020) - Zhou, Yanyan; Li, Yanyan; Wu, Haoyang; Li, Xiang; Yu, Shuaishuai; Wu, Junxiao; Wang, Wenjie; Zhao, Lei
Abstract : An extremely broadband yellow-emitting phosphor Sr8 MgCe(PO4 )7 :Eu 2+ has been realized. Abstract : The combination of binary complementary color phosphors with near-ultraviolet (NUV) light-emitting diode (LED) chips was put forward to lower the energy loss caused by the reabsorption of the combination of tricolor phosphors with NUV LED chips. Thus investigating broadband yellow-emitting phosphors with enriched red components in the spectral range has gained much attention. Here, an extremely broadband yellow-emitting phosphor Sr8 MgCe(PO4 )7 :Eu 2+ with sufficient red component in the spectral region was synthesized. Due to the introduction of Ce into the host, Sr8 MgCe(PO4 )7 shows an emission band with a peak at 375 nm when excited at 310 nm. Meanwhile, Eu 2+ doped Sr8 MgCe(PO4 )7 exhibits an extremely broad yellow emission band with a full width at half-maximum of 175 nm and a peak located at about 598 nm, due to the 5d–4f transitions of Eu 2+ ions substituting five Sr 2+ sites. The excitation peak of the host at 310 nm was detected in the excitation spectrum of Sr8 MgCe(PO4 )7 :Eu 2+ monitored at 598 nm, indicating the energy transfer from the host to Eu 2+, which was also proved by the decay curves. On the other hand, the excitation band at about 400 nm due to the 4f–5d transitions of Eu 2+ was also detected in the excitation spectrum of Sr8 MgCe(PO4 )7 :Eu 2+, and this matches well with the NUV LED chips. Moreover, the energy transfer between Eu 2+ ions at different crystallographic sites was demonstrated by time-resolved photoluminescence (TRPL) spectra. A white LED with a CRI ( R a ) of 82.88 and a CCT of 4238 K was prepared through a 400 nm NUV LED chip, Sr8 MgCe(PO4 )7 :Eu 2+ and BaMgAl10 O17 :Eu 2+ (BAM:Eu 2+ ). These results pave the way for designing better Eu 2+ -doped phosphors for NUV WLEDs with binary complementary color phosphors.